The quantum dot vs. organic dye conundrum for ratiometric FRET-based biosensors: which one would you chose?. Issue 22 (24th May 2022) - Grazon, Chloé; Chern, Margaret; Lally, Patrick; Baer, R. C.; Fan, Andy; Lecommandoux, Sébastien; Klapperich, Catherine; Dennis, Allison M.; Galagan, James E.; Grinstaff, Mark W.
Abstract : We report a combined experimental and computational study to systematically compare the nature of the dye, i.e., organic fluorophore vs. inorganic nanoparticle, and the position of the FRET donor or acceptor on the biosensor performances. Abstract : Förster resonance energy transfer (FRET) is a widely used and ideal transduction modality for fluorescent based biosensors as it offers high signal to noise with a visibly detectable signal. While intense efforts are ongoing to improve the limit of detection and dynamic range of biosensors based on biomolecule optimization, the selection of and relative location of the dye remains understudied. Herein, we describe a combined experimental and computational study to systematically compare the nature of the dye, i.e., organic fluorophore (Cy5 or Texas Red) vs. inorganic nanoparticle (QD), and the position of the FRET donor or acceptor on the biomolecular components. Using a recently discovered transcription factor (TF)–deoxyribonucleic acid (DNA) biosensor for progesterone, we examine four different biosensor configurations and report the quantum yield, lifetime, FRET efficiency, IC50, and limit of detection. Fitting the computational models to the empirical data identifies key molecular parameters driving sensor performance in each biosensor configuration. Finally, we provide a set of design parameters to enable one to select the fluorophore system for future intermolecular biosensors using FRET-based conformational regulation in in vitro assays and new diagnostic devices.